The Effect of the Discovery Learning Model Supported by Anatomical Poster Media on Improving Conceptual Understanding of the Digestive System in Year 5 at SDN 1 Jatimerta - Muhammad Bayu; Susilawati Susilawati; Dewi Yuianawati (Journal of Educational Sciences, 2026)
This study aims to determine the effect of the Discovery Learning model assisted by anatomical poster media on the conceptual understanding of fifth grade students regarding the human digestive system at SDN 1 Jatimerta. The study was motivated by students’ low understanding of science concepts due to teacher centered learning and the limited use of visual learning media. This research employed a quantitative approach using a pre experimental method with a one group pretest posttest design. The sample consisted of 30 fifth grade students. Data were collected through pretest and posttest instruments, classroom observations, and student response questionnaires. Data analysis was conducted using descriptive statistics, the Wilcoxon Signed-Rank Test, and N-Gain analysis. The results showed that students’ conceptual understanding improved significantly after the implementation of the learning model. The average score increased from 43.23 on the pretest to 86.33 on the posttest. The Wilcoxon Signed-Rank Test indicated a significant difference between pretest and posttest scores. In addition, the N-Gain score of 0.7578 was categorized as high. The study concludes that the Discovery Learning model assisted by anatomical poster media has a positive effect on improving students’ conceptual understanding of the human digestive system.